Yield Stability of Dry Bean Genotypes across Nitrogen‐Fixation‐Dependent and Fertilizer‐Dependent Management Systems. Issue 1 (1st January 2016) - Farid, Mehdi; Earl, Hugh J.; Navabi, Alireza
ABSTRACT: Despite the inherent N2 –fixing ability of legumes, the actual symbiotic N2 fixation (SNF) of dry bean ( Phaseolus vulgaris L.) compared with other legumes is relatively low. Accordingly, application of inorganic nitrogen in bean fields has often been recommended to maximize economical yield. The genetic diversity for SNF in common bean may provide the opportunity to develop bean genotypes with stable yield across N‐fertilizer‐dependent and SNF‐dependent production practices. A population of 140 recombinant inbred lines (RILs) of a cross between high and low N‐fixing genotypes, 'Mist' and 'Sanilac', respectively, was evaluated under two different N management conditions, SNF and N fertilizer dependent, across multiple environments. While N management did not significantly affect the overall yield, genotypes responded differentially to SNF‐dependent and N‐fertilizer‐dependent environments. Among the RILs with higher than average yield, the stability analysis identified 6% as generally adapted to all environments, regardless of N management. The study highlights the opportunity to select bean genotypes that maintain their yielding ability under SNF‐dependent management systems.